Adolescent Perceptions of the Integrated Health Service Post (Posyandu Remaja) in Depok, Indonesia: A Cross-Sectional Evaluation Using the CIPP Framework - Kurnaesih, Een; Suryani, Adelia; Raharjo, Agung; Nurul Haq, Siti Zaenab (National Journal of Community Medicine, 2026)
Background: Adolescent reproductive and mental health remain critical public health challenges in Indonesia. The Posyandu Remaja (Adolescent Integrated Health Post) was established to address these needs, yet evidence on adolescents' perceptions of its implementation quality remains limited. The objective was to evaluate adolescent perceptions of Posyandu Remaja implementation quality in Depok City using the Context-Input-Process-Product (CIPP) evaluation framework. Methods: A cross-sectional study was conducted among 142 adolescents aged 10-19 years in Depok, West Java. A validated 62-item researcher-developed questionnaire assessed four CIPP dimensions using a 5-point Likert scale. MANOVA (Pillai's Trace) examined differences across age, sex, and education level. Results: All CIPP dimensions received highly favorable ratings: Product (4.27), Input (4.26), Context (4.22), and Process (4.19). MANOVA revealed no statistically significant differences across demographic subgroups (all p>0.05), with small effect sizes (η²=0.019-0.025). Notable gaps included low cadre availability, irregular personal attendance, and limited openness in discussing mental health. Conclusion: Adolescents perceived Posyandu Remaja favorably across all dimensions, demonstrating high acceptability and equity across demographic groups. Strengthening peer engagement, cadre availability, and interactive participation strategies are recommended to translate positive perceptions into measurable health outcomes.